Merger policy in a quantitative model of international trade - Holger Breinlich; Volker Nocke; Nicolas Schutz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
In a two-country international trade model with oligopolistic competition, we study the conditions on market structure and trade costs under which a merger policy designed to benefit domestic consumers is too tough or too lenient from the viewpoint of the foreign country. Calibrating the model to match industry-level data in the U.S. and Canada, we show that at present levels of trade costs merger policy is too tough in the vast majority of sectors. We also quantify the resulting externalities and study the impact of different regimes of coordinating merger policies at varying levels of trade costs.
Keywords: F12; F13; L13; L44; 330; Mergers and Acquisitions; Merger Policy; Trade Policy; Oligopoly; International Trade